STRATEGI MANAJEMEN PENDIDIKAN DALAM MENGOPTIMALKAN PEMBELAJARAN DEEP LEARNING DI SDN PEMARON 01 - Sugeng Riyadi; Beni Habibi; Embun Karin Azzahra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses educational management strategies for optimizing pedagogical deep learning at SDN Pemaron 01 within the Merdeka Belajar framework. The analysis focuses on the need for deeper student understanding, contextual learning, teacher readiness, and continuous assessment and feedback. Using a qualitative-conceptual approach based on document review and recent literature, this article argues that deep learning must be managed through an integrated cycle: needs-based planning, organization of school resources, active and reflective classroom implementation, evidence-based monitoring and evaluation, and follow-up improvement. The findings indicate that the most relevant strategies for SDN Pemaron 01 are strengthening teacher learning communities, developing contextual teaching modules, integrating formative assessment, implementing reflective academic supervision, and involving parents in supporting a learning culture. Therefore, deep learning can bridge the Merdeka Belajar policy and classroom practices that are more meaningful, mindful, joyful, and impactful for students' character and competencies.